Bile duct involvement by hepatocellular carcinoma: A rare occurrence and poor prognostic indicator in bile duct brushing samples. Issue 11 (13th September 2019) - Bhattarai, Shristi; Graham, Rondell P.; Sigel, Carlie S.; Shi, Jiaqi; Gonzalez, Raul S.; Xue, Yue; Krasinskas, Alyssa M.; HooKim, Kim; Adsay, Volkan; Reid, Michelle D.
Abstract : Background: Hepatocellular carcinoma (HCC) rarely involves the biliary tree and may be inadvertently sampled on bile duct brushings (BDBs). Methods: The pathology archives of 5 institutions were searched for BDBs with HCC involvement. Results: A total of 17 BDBs from 14 patients were obtained. There was a male:female ratio of 6:1; the median age of the patients was 59.5 years (range, 22‐80 years). The median hepatic tumor size was 6.2 cm (range, 2.2‐13.0 cm). HCC risk factors included viral hepatitis (5 patients), cirrhosis (5 patients), hemochromatosis (1 patient), and alcoholic steatohepatitis (1 patient). Jaundice with elevated bilirubin, liver enzymes, and α‐fetoprotein was common. Endoscopic retrograde cholangiopancreatography demonstrated bile duct dilatation, polypoid intraductal masses (5 samples), clots/debris (2 samples), or strictures (4 samples). All BDBs had single and clustered large cells with naked atypical nuclei, granular cytoplasm, high nuclear/cytoplasmic ratios, and nuclei with prominent macronucleoli. Less common findings included clear/microvesicular cytoplasm (35%), papillae (29%), and anisonucleosis (35%). Classic HCC features (widened trabeculae [35%], endothelial wrapping [24%], multinucleation [24%], and cytoplasmic bile pigment [35%]) were uncommon. A total of 11 BDBs were diagnosed as malignant (10 with HCC and 1 with cholangiocarcinoma), 2 were diagnosed as atypical, and 1 BDB was diagnosed as negative; approximately two‐thirds were found to have polysomy on fluorescence in situ hybridization. Approximately 71% of patients died of disease at a median of 3.5 months. Conclusions: HCC may extend into the intrahepatic and/or extrahepatic biliary tree, causing masses and/or strictures that may be sampled on BDB. Although cytologically malignant, the classic features of HCC are uncommon, which can cause misdiagnosis. Cytopathologists should be mindful of this differential when evaluating BDBs, particularly when concomitant liver masses and/or HCC risk factors are present. Because of the associated high mortality and rapid rate of death, its presence should be conveyed clearly in pathology reports. Abstract : Biliary tree involvement by hepatocellular carcinoma (HCC) may result in tumor sampling by bile duct brushing. Cytopathologists should be mindful of this differential, particularly when concomitant liver masses and/or HCC risk factors are present.